Gênero e discursos online: um estudo discursivo das identidades e narrativas compartilhadas de mulheres no Facebook - Lessa, Monique de Mesquita (2023)
Observations of the changes in the use of language caused by the emergence of social media and the growing tensions in gender relations in the Brazilian scenario motivated this investigation about shared stories and gender identities (re)produced by online feminist campaigns. The main objective of this study is to analyze the construction of these stories and identities on Facebook. For that purpose, some posts connected to the campaigns #primeiroassédio and #meuamigosecreto (free translation: #firstharassment and #mysecretmalefriend) were selected as these hashtags were boosted by Brazilian women who exposed different forms of violence experienced by them in their lives as well as inequalities associated to gender as a social structure in decolonial perspective. This research adopts the following approaches/authors in terms of methodology/theoretical framework: Critical Discourse Analysis (CDA) via the dialectical-relational approach by Chouliaraki; Fairclough, 1999; Fairclough, 2001; 2003, the feminist approach (Lazar, 2007), and the Latin-American perspective (Resende, 2019); Narrative Analysis – more specifically the small stories approach (Georgakopoulou, 2007) and shared stories (Page, 2018), as well as Gender Studies, which guide the adoption of an intersectional approach (Crenshaw, 2002; Collins; Bilge, 2016) to investigate the inequalities (re)produced by different elements of the social division. Additionally, with the aim of noticing the meanings, motivations, intentions, and beliefs that are part of the analyzed stories/social practices, some procedures were adopted from the Discourse-Centred Online Ethnography (Androutsopoulos, 2008), such as semi-structured interviews with the authors of the posts that compose the research data. As suggested by the discursive approaches adopted in this study, stories are understood as social practices (De Fina; Georgakopoulou, 2008). Therefore, linguistic resources that express evaluations (Fairclough, 2003; Martin; White, 2005), intertextual relations, positioning of the characters in stories (Bamberg, 1997), and the alignments conducted between the interlocutors were analysed as modes of (re)construction of both discourses and identities in the situational level as well as in wider social processes. The correlation between approaches and analytical categories allowed us to recognize how shared stories through the hashtags mentioned above are emancipatory social practices in which multisemiotic/technological resources are utilized to represent and problematize hegemonic beliefs and discourses about violence and gender identities. As a result, it is attainable to consider shared stories as forms of action and interaction that (re)construct knowledge and emancipatory identities, which in turn, boost social change.